2021
DOI: 10.2106/jbjs.21.00688
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction Recovery and Rehabilitation

Abstract: Background: The success of anterior cruciate ligament (ACL) reconstruction is influenced by effective rehabilitation. Previously published, comprehensive systematic reviews evaluating rehabilitation after ACL reconstruction have studied Level-I and II evidence published through 2012. Interval studies continue to evaluate the efficacy of various rehabilitative modalities.Methods: A total of 824 articles from 2012 to 2020 were identified using multiple search engines. Fifty Level-I or II studies met inclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 61 publications
(130 reference statements)
2
43
0
Order By: Relevance
“…Ligament reconstruction provides a solution for ACL injury. However, due to the need for a semitendino-femoral graft for cruciate ligament reconstruction, with the continuous updating of technology, new bionic materials may be added, and early fixation, delayed weight-bearing and protection of grafts are the current concerns of sports rehabilitation patients [24].…”
Section: Technologies Directly Related To 4irmentioning
confidence: 99%
“…Ligament reconstruction provides a solution for ACL injury. However, due to the need for a semitendino-femoral graft for cruciate ligament reconstruction, with the continuous updating of technology, new bionic materials may be added, and early fixation, delayed weight-bearing and protection of grafts are the current concerns of sports rehabilitation patients [24].…”
Section: Technologies Directly Related To 4irmentioning
confidence: 99%
“…A systemic assessment of 15 research found weak evidence that functional knee bracing lowers the re-injury rate. However, functional knee bracing may benefit via in vivo knee kinematics after ACL surgery [29][30][31] .…”
Section: Final Postoperative Obstaclesmentioning
confidence: 99%
“…Another recent meta-analysis including nine studies on various knee disorders found that muscle strength increases were comparably superior for LL-BFRT, and HL-RT compared to LL-RT, with pain improvement superior for LL-BFRT compared to LL-RT and HL-RT [142]. Systematic reviews have also found benefit of LL-BFRT for increasing muscle strength and function in clinical patients during rehabilitation for pre-and post-operative anterior cruciate ligament (ACL) reconstruction [143][144][145][146][147], knee surgery [148], osteoarthritis [149,150], various knee conditions [151][152][153][154], muscular atrophy [155], sarcopenia [156], and elderly patients at risk for various musculoskeletal conditions [113][114][115][116]. The safety of BFRT in musculoskeletal rehabilitation has also been assessed as comparable to standard exercise therapy, with a systematic review of 19 studies finding that the likelihood of adverse events is not increased with BFRT, despite suggestions of potential safety concerns [88].…”
Section: Bfrt Musculoskeletal Rehabilitation Outcomesmentioning
confidence: 99%